ANALISIS IMPLEMENTASI AKAD MURABAHAH DALAM PEMBIAYAAN (KPR) IB FASILITAS LIKUIDITAS PEMBIAYAAN PERUMAHAN PADA PT. BANK SUMUT SYARIAH KCP HM JONI - Widya Alvina Cerasa; Rahmat Kurniawan (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the implementation of the murabahah contract in the financing of Home Ownership Credit (KPR) iB under the Housing Finance Liquidity Facility (FLPP) at PT. Bank Sumut Syariah KCP HM Joni. Often establishes transaction processes that still resemble conventional patterns. There is a lack of costumer understanding regarding the strucrure of the murabahah contract, as well as administrative and technical obstacles that cause the implementation to not fully comply with sharia principles this indicates that, although the contract is labeled as sharia based it’ s implementation still tends to prioritize minimizing risks on the part off Bank Sumut Syariah KCP HM joni. The results indicate that the implementation of the murabahah contract in KPR iB FLPP generally complies with the provisions of the DSN-MUI Fatwa and sharia banking regulations. The process begins with the submission of an application, verification of eligibility, purchase of the house by the bank from the developer, determination of the selling price that includes the bank's profit margin, and signing of the contract between the bank and the customer. However, challenges were identified, including payment delays, limited customer understanding of the murabahah concept, and relatively lengthy administrative procedures. To address these issues, the bank is advised to enhance customer education, expedite administrative processes, and strengthen payment monitoring systems. The findings of this study are expected to provide input for Islamic banking in improving the effectiveness of KPR iB FLPP financing based on the murabahah contract. The results of this research are expected to provide several benefits. For academics, it serves as a reference in developing knowledge, particularly in the field of Islamic banking and the application of the murabahah contract. For banking practitioners, it offers input and evaluation to ensure that the implementation of the murabahah contract aligns with sharia principles and improves customer service. For the public, this study can be a source of information and consideration in choosing Islamic home financing products that comply with sharia principles. Furthermore, the research contributes to enhancing Islamic financial literacy among the community. Keywords: Murabahah Contract, KPR iB FLPP